Personality and Cognitive Factors Related to Completing Extra Credit Assignments - Myers, Charlsie A; Hatchel, Jennifer (International journal for the scholarship of teaching and learning, 2019)
We explored the differences in academic achievement, personality, and cognitive factors among students who did and did not do extra credit. A total of 276 undergraduate students enrolled in introductory or upper-level psychology and biology courses were surveyed following their final exams to determine levels of academic self-efficacy, metacognitive ability, and a variety of other demographic factors. We conducted a 2 (Extra Credit: Completed or Not Completed) x 2 (Course Level: Introductory or Upper-level) x 4 (Final Course Grade: "A", "B", "C", or "D/F") between-subjects MANOVA with academic self-efficacy and measures of metacognitive ability as dependent variables. Our results indicated that Academic self-efficacy and Regulation of Cognition metacognition scores differed based on these factors. The implications for how course-specific feedback and improved awareness of metacognition can improve student achievement related to our findings and future research directions are discussed.